Synthesis and high frequency characterization of carbon nanotubes - Liu, Luming (2013)
This project focuses on metallic multi-walled carbon nanotubes (MWNTs) in light of next generation RF applications. CNTs have become a strong alternative material for nanometer RF applications in the past few years. CNTs possess the high potential to compete with or even outperform the current materials used in antennas and interconnectors. The main objective of this project is to investigate the unique RF properties of CNTs for future RF applications up to 40 GHz. This project includes the synthesis of CNTs, coplanar waveguide fabrication and RF characterization.